Exploring the perceived role of brand identity in growing small business in the boutique retail jewellery sector - Buccas, Asheeqah (The IIE, 2021)
Studies in the literature show that in most countries, SMEs make up between 95 to 99 percent of businesses and contribute 70 percent to employment. In South Africa, it is estimated that close to 91 percent of businesses are classified as SMEs, contributing between 52 – 57 percent to GDP and 61 percent to employment. These figures would suggest that SMEs could be contributing more towards South Africa’s GDP and employment if they had the resources and support to do so. A recent report estimates the fashion and luxury jewellery segment to account for approximately 17 percent of apparel spending. Globally, consumers spend approximately $348.5 billion annually on jewellery, with the sector predicted to grow significantly over the next five years, and this research study is focused on how brand and brand identity can be used to help with the growth of this segment. Small businesses are at a disadvantage as they do not have the same capabilities and resources to compete at the same level as big business. Additionally, most of the research in branding focuses on big business, with the learnings not generally transferable to SMEs due to their distinct and unique characteristics. The purpose of this qualitative study is fourfold: firstly to explore the role of brand identity in small independent boutique jewellery stores in the Gauteng region, secondly to investigate whether small businesses in the retail jewellery sector engage in building brand identity, and thirdly to understand whether brand and brand identity helps to grow the business. Lastly, to add to the limited body of existing research as it relates to small independent boutique jewellery retailers. The researcher conducted semi-structured interviews with three SME retail jewellery boutique owner-managers, customers, and suppliers (nine data sets). These interviews were built around the Aaker and Joachimsthaler (2009) brand identity framework (deductive). Major findings for boutiques 1 and 2 include a lack of focus on brand or brand identity as well a strong link to the owner-manager as the brand rather than the retail store itself. Their perception was that building strong customer relationships were more important than brand building, and it followed that their marketing activities tended to focus on word of mouth. They also felt that they were offering a niche product and service without much competition. Major findings for boutique 3 include a much stronger focus on branding and marketing activities, as well as a strong understanding of what their competitors were doing. Customer service orientation was a key finding for all three boutiques, echoed by both owner-managers and customers as a differentiator from commercial retail jewellery stores. In conclusion, using insights from this study, the researcher recommends further research and exploration of additions to brand and brand identity guidelines for SMEs which flows from the primary business aims of the retail store as the starting point, with customer relationship management as a focal point.
Keywords: Brand identity; Small Medium Enterprise; SMEs; Brand building; Retail jewellery; Branding